Trig
posted by Tara .
Simplify sin x cos^2xsinx
Here's my book's explanation which I don't totally follow
sin x cos^2xsinx=sinx(cos^2x1)
=sinx(1cos^2x)
=sinx(sin^2x) (Where does sine come from and what happend to cosine?)
=sin^3x

sin x cos^2xsinx=sinx(cos^2x1) they took out a common factor of sinx
=sinx(1cos^2x) recall that sin^2x + cos^2x = 1, and then 1cos^2x = sin^2x.
Notice they had cos^2x1 which is (1cos^2x). Also notice that there is now a  in front of the sinx
=sinx(sin^2x) (Where does sine come from and what happend to cosine?)
=sin^3x
does it make sense now?